1989
DOI: 10.1093/oxfordjournals.humrep.a136942
|View full text |Cite
|
Sign up to set email alerts
|

Quality control in an in-vitro fertilization laboratory: use of human sperm survival studies

Abstract: A bioassay procedure is described for quality control testing of various disposable items used in routine IVF procedures. This bioassay is performed over 4 days and uses the survival of human sperm in vitro at room temperature to assess which products are suitable for use. New products were tested for cytotoxicity using a general screening method and subsequent batches of every suitable item tested to detect interbatch variation. Products were considered suitable or unsuitable for use depending upon a calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 8 publications
2
48
0
Order By: Relevance
“…While the mouse embryo assay is the most common QC method used by manufacturers, the human sperm motility assay is commonly used by IVF laboratories [11,20]. The HSMA is an easy and inexpensive assay that detects toxicity of certain laboratory materials [12]. Sensitivity of the HSMA is comparable or superior to those of the mouse embryo assay for latex gloves and some laboratory supplies [11,21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the mouse embryo assay is the most common QC method used by manufacturers, the human sperm motility assay is commonly used by IVF laboratories [11,20]. The HSMA is an easy and inexpensive assay that detects toxicity of certain laboratory materials [12]. Sensitivity of the HSMA is comparable or superior to those of the mouse embryo assay for latex gloves and some laboratory supplies [11,21].…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that the 1-cell MEA was twenty times more sensitive than the HSMA for peroxides in mineral oil, indicating that the HSMA should not be used for screening mineral oil for peroxides. Though sperm were not exposed directly to the treated oil, the objective of this experiment was to test the HSMA as it is commonly used for QC testing [11,12]. The 1-cell MEA was the most sensitive assay for peroxide in oil of the three most commonly used QC assays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1989, Critchlow et al reported that the toxic powder of the gloves could be transferred to the embryo transfer catheter by simple touch and that physicians should wear un-powdered gloves at the time of embryo transfer [5]. There is no doubt now that the powder of the gloves used is toxic when it comes in contact with embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that surgical glove powder particles would inhibit the growth of adult human vascular endothelial cells in cultures [3]. Simply touching the medium of embryo growth or the embryo transfer catheter the surgical glove powder was shown to be embryo-toxic by mouse embryos assay or by human sperm survival assay [4,5].…”
Section: Introductionmentioning
confidence: 99%